Management of Neuropsychiatric Symptoms of Dementia in Clinical Settings: Recommendations from a Multidisciplinary Expert Panel - Kales, Helen C. (2014)
Non-cognitive neuropsychiatric symptoms (NPS) of dementia include aggression, agitation, depression, anxiety, delusions, hallucinations, apathy, and disinhibition. These affect dementia patients nearly universally across dementia stages and etiologies. NPS are associated with poor patient and caregiver outcomes including excess morbidity and mortality, increased health care utilization, and earlier nursing home placement, as well as caregiver stress, depression and reduced employment. While there is no FDA-approved pharmacotherapy for NPS, psychotropic medications are frequently used to manage these symptoms. However, in the few cases of proven pharmacologic efficacy, benefit may be off set by significant risk of adverse effects. Non-pharmacologic treatments, typically considered first-line, also show evidence for efficacy as well as a limited potential for adverse effects. However, their uptake as preferred treatments remains inadequate in real-world clinical settings. Thus, the field currently finds itself between a “rock and a hard place” in terms of management of these difficult symptoms. It was in this context that the University of Michigan Program for Positive Aging, working in collaboration with the Johns Hopkins Alzheimer’s Disease Research Center and Center for Innovative Care in Aging sponsored and convened a multidisciplinary expert panel in Detroit Michigan in Fall 2011 with three objectives, to: 1) define key elements of care for NPS in dementia; 2) construct an approach describing the sequential and iterative steps of managing NPS in real-world clinical settings that can be used as a basis for integrating non-pharmacologic and pharmacologic approaches; 3) discuss how the approach generated could be implemented in research and clinical care.